Change in Health-Related Quality of Life in Cochlear Implant Recipients in China. (26th March 2022) - Zheng, Wenwen; Cao, Wei; Chen, Shanwen; Li, Yifan; Wang, Yang; Yao, Kun; Qiu, Jianxin
Abstract : Objective . The objective is to assess the benefit of cochlear implants in health-related quality of life among postlingually deaf adults in China. Methods . Seventy-one postlingually deaf adult cochlear implant users in one cochlear implant center in China participated in this study. The HUI3 questionnaire as a measurement evaluated their quality of life. A cross-sectional analysis was conducted. Results . Cochlear implant had made statistically significant improvements in quality of life among postlingually deaf adults. The HUI3 scores were significantly better in four attributes (hearing, speech, emotion, and pain) after a cochlear implant. A positive correlation between change in hearing and improvement in emotion was significant. The change in pain and improvement in emotion also had a positive correlation. The duration of HA and CI use had no impact on the gain in HUI3 scores, and the baseline of hearing and emotion state had an influence on HUI3 gain. Conclusion . This study found cochlear implant users had a greatly improved hearing, speech, emotion, and pain, which made statistically significant improvement in quality of life among postlingually deaf adults. There was a statistically significant association between the change of emotion state and improvement in hearing level. We also found a statistically significant correlation between the reduction of feeling in pain and improvement in emotion. The change of quality of life seemed to be influenced by the primary state of emotion and hearing. We believe the measurement HUI3 is suitable for these patients in China.